1975
DOI: 10.1088/0022-3727/8/5/015
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conduction in dielectrics at high fields

Abstract: A model for the conduction mechanism in polymer insulating materials based on a classical concept is described; the application may possibly be extended beyond polymers. By means of this model, a formula expressing the field dependence of conductivity is derived. The values given by this formula have been checked against published experimental data from several sources, and good agreement was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(32 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…The data show that at electric field below 550 MV/m, the P(MDA/MDI) films display an efficiency of 96%, similar to those of the low loss polymer dielectrics such as biaxially oriented polypropylene (BOPP) [18]. At higher field, the efficiency drops, due to increased conduction at high field [10,[18][19][20].…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The data show that at electric field below 550 MV/m, the P(MDA/MDI) films display an efficiency of 96%, similar to those of the low loss polymer dielectrics such as biaxially oriented polypropylene (BOPP) [18]. At higher field, the efficiency drops, due to increased conduction at high field [10,[18][19][20].…”
Section: Resultsmentioning
confidence: 86%
“…In dielectric polymers, there exist many types of conduction processes, some of which are interface controlled such as the Φ is the barrier height, U is the activation energy, V is the applied voltage, k is the Boltzmann constant, and T is temperature [18][19][20][21][22][23][24][25][26]. All these conductions exhibit non-linear increase with applied field and can become significant at high electric field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation energy E a of the conduction phenomenon obtained through the linear fit using equation (6) • C, such as for polypyromellitimide films [55][56][57], and usually resulting from the conduction current experiments under static polarization. Such conductivity values indicate the semiinsulating character of the PI materials in such a wide temperature range close to the glass transition temperature.…”
Section: -P5mentioning
confidence: 99%
“…[4][5][6]9 The electrical conduction behaviors of PMDA/ODA films have been investigated by several research groups. [10][11][12][13][14][15][16][17][18][19] Sawa et al 13 studied the electric conduction current of PMDA/ODA films at temperatures of 120-180 1C and applied electric fields of 4 À500 kV cm À1 . They concluded that the conduction in the PI films is caused by ionic hopping.…”
Section: Introductionmentioning
confidence: 99%